Selection of Slightly B∗-Continuous Multifunctions - Jain, Pankaj; Basu, Chandrani; Panwar, Vivek (Eurasian Mathematical Journal, 2022)
In the present paper, the existence of quasicontinuous selection for slightly B∗-continuous multifunctions is established.